(3JWHjbGJ CdaG aj GdEOGQI (B:s (3JNUUGJ(B-(3GdEOGQI(B-(3GdJShjb(B-(3EOGQI GdeSJhOYGJ (B/s - (3GdRYHj, gjKes; (3GHh GdRjJ, MSf hBNQhfs ((3YeGf(B: s (3OGQ UaGA(B, s, 2002)
(3fXGe GdQhGJH hTDhf GdehXajf,fXGe GdeSJhOYGJ hGdeHjYGJ, fXGe GdeTJQjGJ(B((3GdWdHjGJ(B)(3, fXGe GdYedGA, fXGe GdEfJGL, fXGe GdTHcGJs
Keywords: (3EOGQI GdCYeGds; (3GdHQeLI GdNWjIs